2018
DOI: 10.1101/385138
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A computational model of loss of dopaminergic cells in Parkinson’s disease due to glutamate-induced excitotoxicity

Abstract: Parkinson's disease (PD) is a neurodegenerative disease associated with progressive and inexorable loss of dopaminergic cells in Substantia Nigra pars compacta (SNc). A full understanding of the underlying pathogenesis of this cell loss is unavailable, though a number of mechanisms have been indicated in the literature. A couple of these mechanisms, however, show potential for the development of radical and promising PD therapeutics. One of these mechanisms is the peculiar metabolic vulnerability of SNc cells … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(21 citation statements)
references
References 213 publications
(311 reference statements)
1
20
0
Order By: Relevance
“…Accordingly, the establishment of reliable computational models to investigate the inner events of the pathogenesis represents a key issue in the field. Current models of neuron and mean-field are predominantly biophysically based and account for several factors that influence the electrophysiology of neurons, such as processing of synaptic inputs, ionic basis of electrical excitability, and the effect of DA [12][13][14][15] . Here, we review the neuron model and mean-field neural model which are of physiological significance.…”
Section: Computational Models Of Ctbg Circuitsmentioning
confidence: 99%
“…Accordingly, the establishment of reliable computational models to investigate the inner events of the pathogenesis represents a key issue in the field. Current models of neuron and mean-field are predominantly biophysically based and account for several factors that influence the electrophysiology of neurons, such as processing of synaptic inputs, ionic basis of electrical excitability, and the effect of DA [12][13][14][15] . Here, we review the neuron model and mean-field neural model which are of physiological significance.…”
Section: Computational Models Of Ctbg Circuitsmentioning
confidence: 99%
“…A more classic example is glutamatergic excitotoxicity imposed by the hyperactivity of the subthalamic nucleus (STN) and other subcortical nuclei induced by dopamine depletion . This concept offers additional possibilities to the decision about where to intervene with a putative disease‐modifying therapy, pointing our attention toward the STN as an appealing target …”
Section: When Where and How To Apply Focused Ultrasound For Diseasementioning
confidence: 99%
“…[47][48][49] This concept offers additional possibilities to the decision about where to intervene with a putative disease-modifying therapy, pointing our attention toward the STN as an appealing target. [49][50][51] Finally, the decision of how to treat is closely related to the decision of where to intervene. We will first discuss the disease-modifying potential of FUS subthalamotomy, a procedure that we are testing for symptomatic efficacy in clinical trials 8 (NCT03454425).…”
mentioning
confidence: 99%
“…In an earlier computational study, we have shown that metabolic deficiency at the systems/network level can lead to neurodegeneration of SNc neurons due to excitotoxicity caused by an overexcited Subthalamic Nucleus (STN) (Muddapu et al, 2018(Muddapu et al, , 2019Muddapu and Chakravarthy, 2017). As a further step in understanding the PD pathophysiology, in the present study, we proposed to model the effects of metabolic deficiencies in SNc at subcellular level.…”
Section: Introductionmentioning
confidence: 99%
“…While existing treatments manage the symptoms of PDsometimes with miraculous effecta genuine cure demands an understanding of the root cause of SNc cell loss. Recently, a new approach towards PD etiologythat metabolic deficiencies at subcellular/cellular/network level can be a major cause of SNc cell loss in PDwas gaining attention (Bolam and Pissadaki, 2012;Muddapu et al, 2018Muddapu et al, , 2019Muddapu and Chakravarthy, 2017;Pacelli et al, 2015;Wellstead and Cloutier, 2011).…”
Section: Introductionmentioning
confidence: 99%